EFFECT OF SPLITTING FACTOR IN THE MONTE CARLO SIMULATION OF PERCENTAGE DEPTH DOSE CURVE USING PHOTON BEAM - Aula Nurrohman, Nafi'
The usage of Monte Carlo method in radiotherapy increased rapidly since 1970 alongside with the increasing computing Power. At the earlier stage, the Monte Carlo application only simulate simple geometry like infinite parallel slabs or cylinder. Today, Monte Carlo can be used in a very complex 3Dshape. The accuration of dose calculation using Monte Carlo is limited to statistical noise. That statistical noise can be easily reduced by increasing the number of histories. However, a larger histories will make the simulation run longer. To reduce the time used in each run of simulation, a Variancereduction Technique (VRT) can be used. Splitting is one of the most used VRT in Monte Carlo. It is a technique where a particle will be split into a few other particles. This technique wills reduce the error of the simulation, but the simulation time will increase. This research will look St the effect of different splitting factor toward error, simulation and the dose distribution on phantom that is measured from the PDD. The result of simulation shows that the splitting factor is effecting the error of the simulation result and how fast the simulation is performed. A bigger splitting factor will make the simulation process go longer but with its error become smaller. On the other hand, the depth of the maximum doses is not affected by the variation of splitting factor.